Sildenafil (viagra) izboljša erektilno disfunkcijo pri dializnih bolnikih - naše prve izkušnje - Vujkovac, Bojan (Zdravniški vestnik, 2002)
Background. Male patients with end stage renal disease often report erectile dysfunction, which is very common especially in younger males. Impotence is reported to exceed 50% in male chronic renal failure patients, and is present in 65% of such patients undergoing hemodialysis. Numerous etiological factors have been reported as possible cause for sexual dysfunction. Sildenafil (Viagra), a potent specific inhibitor of cGMP phosphodiesterase, was used in this case study to improve erectile dysfunction in dialysis male patients. Methods and results. During 12 weeks we treated 4 dialysis patients. 2 patients were treated with peritoneal dialysis and 2 patients were in the program of chronic hemodialysis. All patients were in the program of dialysis for more than 24 months, and reported erectile dysfunction and impotence afterthey had started with dialysis treatment. Sildenafil was used in the treatment The dosage schedule for sildenafil was 50mgž week orally for 2 weeksfollowed by 100 mgžweek for the next 10 weeks if there was no effect on initial dosage. Efficacy of treatment was evaluated by means of the International lndex of Erectile Dysfunction. All 4 patients reported no significant effect on initial dose. With higher dose of sildenafil treatment was overwhelmingly successful, with reported prolonged improvement of erectiledysfunction for 42 to 72 hours. Side effects were present only in 1 patient who had severe headaches after higher dose. No patients experienced priapism. Conclusions. There have been only few reports in the literature on the use of sildenafil in dialysis patients. Our small case study suggests thatsildenafil could be successfully and safely used for treatment of erectiledysfunction also in dialysis patients. A large trial would be necessary to confirm the efficacy of the drug for this specific group of patients.
Keywords: Avtorji domačini; Dializni bolniki; erekcija; Erektilna disfunkcija; Hemodializa; Koroška krajina; motnje; Sildenafil; Viagra